Derivation: An Efficient Way of Enhancing English Vocabulary - Nadia, Refat (Universiti Malaysia Pahang, 2015)
In this paper, the concept of derivation is studied and its relation to English vocabulary learning is discussed. A structured based derivation process, which is an efficient way of enhancing English vocabulary compared to traditional vocabulary learning such as dictionary based and text based approaches, is proposed. This structural process helps to grow learners’ interest to build more words in a faster way. Such a dynamic and emergent approach of enriching English words truly emerges with its important implications for the teaching of English in language learning classes. In order to ensure the efficiency of this process, experimental design was employed to test learners’ ability to enhance their vocabulary knowledge. Thirty students participated in this study, and they were divided into an experimental group and two control groups, with the administration of pre-test and posttest. The treatment is a brief training on vocabulary enhancing methods (i.e., dictionary, text and derivation based learning). The results reveal that students who used the derivation based learning (55%) were able to enhance their vocabulary knowledge better compared to those who were exposed to dictionary based learning (13%) and text based learning (22%). The outcome confirms the effectiveness of derivation.